Diagnostic performance of mobile cone beam computed tomography versus conventional multi-detector computed tomography in orbital floor fractures: a study on human specimens. Issue 2 (February 2021) - Lacagne, A.S.; Brumpt, E.; Barrabé, A.; Pomero, E.; Chatelain, B.; Grillet, F.; Weber, E.; Malakhia, A.; Pons, M.; Aubry, S.; Meyer, C.; Sigaux, N.; et al.
Abstract: The aim of this study was to evaluate the diagnostic accuracy of mobile cone beam computed tomography (MCBCT) versus multi-detector computed tomography (MDCT) in orbital floor fractures. Twenty-four fresh cadaver heads were used, and one orbital floor was fractured for each head by transconjunctival approach. MDCT and MCBCT were performed on each of the heads. The images obtained were then analysed independently by eight evaluators. The radiological characteristics of the orbital floor fractures were visualized with good interpretation agreement between the two images. The location of the fracture and enophthalmos were identified in a comparable manner with strong agreement (κ = 0.93 and κ = 0.85, respectively). Measurements of fatty hernias and bone defects showed a strong correlation between the two imaging modalities (Pearson coefficient between 0.64 and 0.71 and between 0.67 and 0.71, respectively). The fracture limits and the presence of bone fragments, an intrasinus fatty hernia, and a fracture of the associated medial orbital wall were visualized in both examinations with good agreement (κ = 0.68, κ = 0.51, κ = 0.57, and κ = 0.46, respectively). The soft tissue study showed superiority for MDCT, with a κ < 0.0009. MCBCT showed good diagnostic performance in the study of orbital floor fracture characteristics.